Exchange Rate Policy and Monetary Strategy Options in the Philippines : The Search for Stability and Sustainability - Houben, Aerdt (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1997)
This paper evaluates the Philippines' experience with different exchange regimes since 1970. It argues that the shift to a flexible regime was crucial to restoring external viability and generating an export-led economic take-off, but that mixed performance in meeting money targets and asymmetric policy reactions to exchange rate pressures have resulted in an uneven inflation performance. Since adoption of a firm nominal anchor for monetary policy would contribute to a more effective control of inflation and thereby to better prospects for sustained growth, the merits of three monetary strategy options are reviewed: stricter adherence to a money supply rule, adoption of an exchange rate peg, and a switch to direct inflation targeting.